2019
DOI: 10.12659/msm.915708
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Optic Nerve Sheath Diameter in Patients Undergoing Epiduroscopy

Abstract: Departmental sources Background: Epiduroscopy is commonly used for the evaluation and treatment of low back pain. Saline with or without local anesthetic addition was used to visualize epidural space structure during this procedure. A rapid increase in epidural space pressure is transmitted into the spinal space to the optic nerve sheath. This study aimed to estimate the effects of epiduroscopy on optic nerve sheath diameter (ONSD) according to the volume of fluid using the ultrasonographic measurement of opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…The cut-off value (4.8 -6.3 mm) observed in this study was considerably higher than previous studies reported (7,15,16). In a study published in 2019, it was stated that the cut-off value was 6.3 mm (5.2 -6.3 mm) (17). In this study, measurements were 6.32 ± 0.88 mm for the right eye and 6.35 ± 0.84 mm for the left eye, while the cut-off value was 9 mm (4.1 -8.2 mm).…”
Section: Discussioncontrasting
confidence: 77%
“…The cut-off value (4.8 -6.3 mm) observed in this study was considerably higher than previous studies reported (7,15,16). In a study published in 2019, it was stated that the cut-off value was 6.3 mm (5.2 -6.3 mm) (17). In this study, measurements were 6.32 ± 0.88 mm for the right eye and 6.35 ± 0.84 mm for the left eye, while the cut-off value was 9 mm (4.1 -8.2 mm).…”
Section: Discussioncontrasting
confidence: 77%
“…Large pressure waves may cause direct injury to pial bridging veins and render the posterior optic nerve ischemic. Rupture of larger veins or arteries may lead to more extensive bleeding in any of the ophthalmic structures and may cause permanent loss of vision ( 21 , 22 ).…”
Section: Effect Of Increased Subarachnoid Pressurementioning
confidence: 99%